A strategic approach to the unfinished fortification agenda: Feasibility, costs, and cost-effectiveness analysis of fortification programs in 48 countries - Fiedler, John L.; Macdonald, Barbara (SAGE Publications, 2009)
Food fortification is a promising strategy for combating micronutrient deficiencies, which plague one-third of the world's population. Which foods to fortify, with which micronutrients, and in which countries remain essential questions that to date have not been addressed at the global level.To provide a tool for international agencies to identify and organize the next phase of the unfinished global fortification agenda by prioritizing roughly 250 potential interventions in 48 priority countries. By explicitly defining the structure and operations of the fortification interventions in a detailed and transparent manner, and incorporating a substantial amount of country-specific data, the study also provides a potentially useful starting point for policy discussions in each of the 48 countries, which—it is hoped—will help to catalyze the development of public–private partnerships and accelerate the introduction of fortification and reduction of micronutrient deficiencies.Forty-eight high-priority countries were identified, and the feasibility of fortifying vegetable oil and sugar with vitamin A and fortifying wheat flour and maize flour with two alternative multiple micronutrient formulations was assessed. One hundred twenty-two country-, food-, and fortification formulation–specific interventions were assessed to be feasible, and the costs of each intervention were estimated. Assuming a 30% reduction in the micronutrient deficiencies of the persons consuming the food, the number of disability-adjusted life years (DALYs) saved by each of the programs was estimated.The cost per DALY saved was calculated for each of the 122 interventions, and the interventions were rank-ordered by cost-effectiveness. It is estimated that the 60 most cost-effective interventions would carry a 10-year price tag of US$1 billion and have costs per DALY saved ranging from US$1 to US$134. The single “best bet” intervention—i.e., the most cost-effective intervention—in each of the 48 countries was identified.This study provides a detailed, transparent, evidence-based approach to defining and estimating the costs and cost-effectiveness of the unfinished global fortification agenda in the 48 priority countries. Other considerations in designing a strategic approach to the unfinished global fortification agenda are also discussed.